Emerging biocompatible nanoplatforms for the potential application in diagnosis and therapy of deep tumors. Issue 2 (9th September 2021) - Guo, Wenna; Chen, Zengzhen; Tan, Longfei; Gu, Deen; Ren, Xiangling; Fu, Changhui; Wu, Qiong; Meng, Xianwei
Abstract: Cancer, as one of the most attention‐grabbing medical problems, has been tried to solve with various methods. With the development of nanotechnology, diagnosis and therapy based on nanoplatforms have become new dawn for overcoming cancer problems. Biocompatible nanoplatforms integrating diagnosis and therapy technology for cancer have been extensively studied. Most of the reported works focus on the diagnosis and therapy of subcutaneous tumor. To promote clinical application, it is of great significance to develop efficient methods for deep tumors. This work reviews the latest research progress and future development prospects for the diagnosis and therapy of deep tumors based on biocompatible nanoplatforms. It mainly introduces four cancer diagnostic technologies (fluorescence imaging (FI), computed tomography (CT), magnetic resonance imaging (MRI), and photoacoustic imaging (PAI)) and four tumor treatment methods (phototherapy, ultrasound therapy, radiotherapy (RT), and microwave therapy (MWT)) based on the nanoplatforms. Several diagnostic techniques and treatment methods are systematically summarized and compared, and the advantages and limitations of different methods in tumors are discussed. At last, the application prospects and challenges of the nanoplatforms for the diagnosis and therapy of deep tumors are discussed. It is hoped that this review will provide some useful information for the research in this field. Abstract : SCHEME 1 . An overview of emerging biocompatible nanoplatforms in diagnosis and therapy. The diagnostic techniques include PI, CT, MRI, and PAI. The treatment methods include phototherapy, ultrasound therapy, RT and MWT.